The Association Between Notching of the Right Ventricular Outflow Tract Flow Velocity Doppler Envelope and Impaired Right Ventricular Function After Acute High-Altitude Exposure - Yuan, Fangzhengyuan; Liu, Chuan; Yu, Shiyong; Bian, Shizhu; Yang, Jie; Ding, Xiaohan; Zhang, Jihang; Tan, Hu; Ke, Jingbin; Yang, Yuanqi; He, Chunyan; Zhang, Chen; et al. (Frontiers in Physiology, 2021)
It has been known that upon high-altitude (HA) exposure, pulmonary artery pressure (PAP) is increased and right ventricular (RV) function is well-preserved. Whereas in patients with pulmonary hypertension, the increase of PAP may trigger the notching of the right ventricular outflow tract Doppler envelope (RVOT notch) and associated with impaired RV function. However, whether HA exposure can induce RVOT notch formation and its impacts on cardiac function remain unclear. A total of 99 subjects were enrolled and ascended from 500 to 4100 m by bus within 2 days. All subjects underwent physiological and comprehensive echocardiographic examination at both low altitude and HA. After HA exposure, there were 20 (20.2%) subjects with RVOT notch [notch (+)] and 79 (79.8%) subjects without RVOT notch [notch (-)]. It was also noted that systolic pulmonary artery pressure (SPAP), mean pulmonary artery pressure (mPAP), pulmonary vascular resistance (PVR), the standard deviation of the time to peak systolic strain in the four mid-basal RV segments (RVSD4), peak velocity of isovolumic contraction period (ICV) and the peak systolic velocity (s’) at the mitral/tricuspid annulus were increased in all of the subjects. Conversely, the pulse oxygen saturation (SpO2), right ventricular global longitude strain (RV GLS), and tricuspid annulus plane systolic excursion (TAPSE/SPAP) were decreased. However, the increases of SPAP, mPAP, PVR, RVSD4 and the decreases of SpO2, RV GLS, TAPSE/SPAP were more pronounced in notch (+) subjects than in notch (-) subjects. Additionally, increased tricuspid ICV and mitral/tricuspid s’ were found only in notch (-) subjects. Thus, this unprecedented study revealed that HA exposure-induced RVOT notch formation was associated with impaired RV function, including failure of the increase in tricuspid ICV and s’, reduction of RV deformation, deterioration in RV-PA coupling, and RV intraventricular synchrony.